On the Lathrobiina of Taiwan (Coleoptera: Staphylinidae: Paederinae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2010)
Primarily based on material collected by Aleš Smetana, Ottawa, in the 1990s, 29 species of Lathrobiina from Taiwan are described and illustrated: Lathrobium alishanum sp. n. (Chiai Hsien: Alishan), L. involutum sp. n. (Taichung Hsien: Hsuehshan), L. anmaicum sp. n. (Taichung Hsien: Anmashan), L. utriculatum sp. n. (Kaohsiung Hsien: Peinantashan), L. extraculum sp. n. (Pingtung Hsien: Peitawushan), L. follitum sp. n. (Pingtung Hsien: Peitawushan), L. houhuanicum sp. n. (Nantou Hsien: Houhuanshan), L. nenkaoicum sp. n. (Nantou Hsien: Nenkaoshan), L. tarokoense sp. n. (Hualien Hsien: Taroko National Park), L. alesi sp. n. (Taichung Hsien: Hsuehshan), Platydomene sinuosa sp. n. (Ilan Hsien), Lobrathium (Lobrathium) nigripenne sp. n. (Chiai Hsien: Alishan), L. (L.) bilobatum sp. n. (Taiwan: widespread), L. (L.) extensum sp. n. (Taichung Hsien), L. (L.) bipeniculatum sp. n. (Ilan Hsien: Chyr Duan), L. (L.) penicillatum sp. n.(Nantou: Shanlinchi), L. (L.) pedes sp. n. (Hualien and Ilan Hsien), L. stimulans sp. n. (Kaohsiung: Peinantashan), L. sororium sp. n. (Kaohsiung: Kuanshan), L. duplehamatum sp. n.(Nantou Hsien), L. smetanai sp. n. (Kaohsiung: Peinantashan), L. furcillatum sp. n. (Pingtung Hsien: Peitawushan), L. cornutissimum sp. n.(Kaohsiung: Peinantashan), L. bisagittatum sp. n. (Ilan and Taoyuan Hsien), L. digitatum sp. n. (Chiai and Nantou Hsien: Yushan), L. bidigitatum sp. n. (Kaohsiung: Peinantashan), L. spoliatum sp. n. (Taichung Hsien: Hsuehshan), L. kuanicum sp. n. (Kaohsiung Hsien: Kuanshan), and L. coalitum sp. n. (Nantou: Nenkaoshan). Several additional Lobrathium species were identified, but remain unnamed, since they are represented only by females. Two apparently monophyletic species groups are established, the Lathrobium involutum group with ten locally endemic species, all of them newly described, and the Lobrathium stimulans group including thirteen named species with more or less restricted distributions, only one of which was described previously. Several species of the L. stimulans group lack the submarginal line of the elytra, traditionally one of the key characters separating Lobrathium Mulsant & Rey, 1878 from most other lathrobiine genera, but evidently secondarily reduced in these species. A key to the Lobrathium species of Taiwan is provided. The genus Lobrathium, as well as Lobrathium sibynicum Zheng, 1988 are recorded from Taiwan for the first time. The following binomina are established: Lobrathium taiwanense (Watanabe, 1998), comb. n. (ex Lathrobium), and Tetartopeus bimaculatus (Li, Tang & Zhu, 2007), comb. n. (ex Lobrathium). Additional records - the first records sínce the original description - are reported for Lathrobium shaolaiense Watanabe, 1998.KeywordsColeoptera, Staphylinidae, Paederinae, Lathrobium, Lobrathium, Platydomene, Tetartopeus, Palaearctic region, Taiwan, species groups, new species, new combinations, new records, key to species.Nomenclatural Actsalesi Assing, 2010 (Lathrobium (Lathrobium)), spec. nov.alishanum Assing, 2010 (Lathrobium (Lathrobium)), spec. nov.anmaicum Assing, 2010 (Lathrobium (Lathrobium)), spec. nov.extraculum Assing, 2010 (Lathrobium (Lathrobium)), spec. nov.follitum Assing, 2010 (Lathrobium (Lathrobium)), spec. nov.houhuanicum Assing, 2010 (Lathrobium (Lathrobium)), spec. nov.involutum Assing, 2010 (Lathrobium (Lathrobium)), spec. nov.nenkaoicum Assing, 2010 (Lathrobium (Lathrobium)), spec. nov.tarokoense Assing, 2010 (Lathrobium (Lathrobium)), spec. nov.utriculatum Assing, 2010 (Lathrobium (Lathrobium)), spec. nov.bidigitatum Assing, 2010 (Lobrathium), spec. nov.bisagittatum Assing, 2010 (Lobrathium), spec. nov.coalitum Assing, 2010 (Lobrathium), spec. nov.cornutissimum Assing, 2010 (Lobrathium), spec. nov.digitatum Assing, 2010 (Lobrathium), spec. nov.duplehamatum Assing, 2010 (Lobrathium), spec. nov.furcillatum Assing, 2010 (Lobrathium), spec. nov.kuanicum Assing, 2010 (Lobrathium), spec. nov.smetanai Assing, 2010 (Lobrathium), spec. nov.sororium Assing, 2010 (Lobrathium), spec. nov.spoliatum Assing, 2010 (Lobrathium), spec. nov.taiwanense (Watanabe, 1998) (Lobrathium), comb. nov. hitherto Lathrobium taiwanense Watanabe, 1998bilobatum Assing, 2010 (Lobrathium (Lobrathium)), spec. nov.bipeniculatum Assing, 2010 (Lobrathium (Lobrathium)), spec. nov.extensum Assing, 2010 (Lobrathium (Lobrathium)), spec. nov.nigripenne Assing, 2010 (Lobrathium (Lobrathium)), spec. nov.pedes Assing, 2010 (Lobrathium (Lobrathium)), spec. nov.penicillatum Assing, 2010 (Lobrathium (Lobrathium)), spec. nov.stimulans Assing, 2010 (Lobrathium (subgenus?)), spec. nov.sinuosa Assing, 2010 (Platydomene), spec. nov.bimaculatus (Li, Tang & Zhu, 2007) (Tetartopeus), comb. nov. hitherto Lobrathium bimaculatus Li, Tang & Zhu, 2007